In-situ plasma treatment and low-temperature lithicone protective layer for interfacial stability of ultrathin Li metal anodes - Ha Yeon Kwon; Kyu Moon Kwon; Min Jung Choi; Syed Jazib Abbas Zaidi; Muhammad Abdul Basit; Ji-Hoon Ahn; Woo-Hee Kim; Seung-Jeong Oh; Hyo Rang Kang; Tae Joo Park (Chemical Engineering Journal, 2026)

Age- and sex- related patterns in hematobiochemical and anthropometric parameters of Macaca monkeys - Hyeon-Mu Cho; Se-Hee Choe; Hye-Ri Park; Ja-Rang Lee; Min-Gyeong Ko; Yun-Jung Lee; Kang Jin Jeong; Bon Sang Koo; Kyung Seob Lim; Gyu-Seo Bae; Eun Su Jeon; Philyong Kang; et al. (GeroScience, 2026)

Prediction and application on the first flowering date of June-bearing strawberry cultivars using Ensemble-based Machine learning with primary temperature values - Tae Yeon Lee; Yu Hyun Moon; Ha Seon Sim; Soo Bin Jung; Ui Jeong Woo; Ha Rang Shin; Yong Jun Kim; Na Kyoung Kim; Jung Su Jo; Sung Kyeom Kim (Computers and Electronics in Agriculture, 2026)

Decreasing annual pollen loads in evergreen needleleaf species (Pinaceae) by the earlier end of the spring pollen season - Jongho Kim; Kyu Rang Kim; Mae Ja Han; Yoori Cho; Sujong Jeong (Agricultural and Forest Meteorology, 2025)

Valorizing tail gas for superior hydrocarbon output in CO2-based Fischer-Tropsch synthesis - Jingyu Chen; Leiyu Zhang; Hae-Gu Park; Ji-Eun Min; Hyung-Ki Min; Jeong-Rang Kim; Chundong Zhang; Ki-Won Jun; Seok Ki Kim (Chemical Engineering Journal, 2025)

CeO2-conjugated CoFe layered double oxides as efficient non-noble metal catalysts for NH3-decomposition enabling carbon-free hydrogen production - Su-Un Lee; Thien An Le; Youngmin Kim; You-Jin Lee; Jeong-Rang Kim; Tae-Wan Kim; Kwang-Eun Jeong; Ho-Jeong Chae (Chemical Engineering Journal, 2024)

Multiple Injections of Adipose-Derived Stem Cells Improve Graft Survival in Human-to-Rat Skin Xenotransplantation through Immune Modulation - Sungmi Jeon; Iljin Kim; Yi Rang Na; Ki Yong Hong; Hak Chang; Seung Hwan Kim; Yu Jin Jeong; Jee Hyeok Chung; Sang Wha Kim (Tissue Engineering and Regenerative Medicine, 2023)

A preliminary study about the potential risks of the UV-weathered microplastic: The proteome-level changes in the brain in response to polystyrene derived weathered microplastics - Hee-Yeon Kim; Janbolat Ashim; Song Park; Wansoo Kim; Sangho Ji; Seoung-Woo Lee; Yi-Rang Jung; Sang Won Jeong; Se-Guen Lee; Hyun-Chul Kim; Young-Jae Lee; Mi Kyung Kwon; et al. (Environmental Research, 2023)

Reduced fertility caused by meiotic defects and micronuclei formation during microsporogenesis in xBrassicoraphanus - Hosub Shin; Hye Rang Park; Jeong Eun Park; Seung Hwa Yu; Gibum Yi; Jung Hyo Kim; Wonjun Koh; Hyun Hee Kim; Soo-Seong Lee; Jin Hoe Huh (Genes & Genomics, 2021)
Background Hybridization and polyploidization events are important driving forces in plant evolution. Allopolyploids formed between different species can be naturally or artificially created but often suffer from genetic instability and infertility in successive generations. x Brassicoraphanus is an intergeneric allopolyploid obtained from a cross between Brassica rapa and Raphanus sativus , providing a useful resource for genetic and genomic study in hybrid species. Objective The current study aims to understand the cause of hybrid sterility and pollen abnormality in different lines of synthetic x Brassicoraphanus from the cytogenetic perspective. Methods Alexander staining was used to assess the pollen viability. Cytogenetic analysis was employed to monitor meiotic chromosome behaviors in pollen mother cells (PMCs). Origins of parental chromosomes in x Brassicoraphanus meiocytes were determined by genome in situ hybridization analysis. Results The x Brassicoraphanus lines BB#4 and BB#6 showed high rates of seed abortion and pollen deformation. Abnormal chromosome behaviors were observed in their PMCs, frequently forming univalents and inter-chromosomal bridges during meiosis. A positive correlation also exists between meiotic defects and the formation of micronuclei, which is conceivably responsible for unbalanced gamete production and pollen sterility. Conclusion These results suggest that unequal segregation of meiotic chromosomes, due in part to non-homologous interactions, is responsible for micronuclei and unbalanced gamete formation, eventually leading to pollen degeneration and inferior fertility in unstable x Brassicoraphanus lines.

Genome divergence in Brassica rapa subspecies revealed by whole genome analysis on a doubled-haploid line of turnip - Hye Rang Park; Taegu Kang; Gibum Yi; Seung Hwa Yu; Hosub Shin; Geon Woo Kim; Jeong Eun Park; Ye Seul Kim; Jin Hoe Huh (Plant Biotechnology Reports, 2019)

Genetic diversity patterns and domestication origin of soybean - Soon-Chun Jeong; Jung-Kyung Moon; Soo-Kwon Park; Myung-Shin Kim; Kwanghee Lee; Soo Rang Lee; Namhee Jeong; Man Soo Choi; Namshin Kim; Sung-Taeg Kang; Euiho Park (Theoretical and Applied Genetics, 2019)

Identification of L1ASP-derived chimeric transcripts in lung cancer - Ja-Rang Lee; Yi-Deun Jung; Yun-Ji Kim; Hee-Eun Lee; HoIm Jeong; Heui-Soo Kim (Genes & Genomics, 2014)

Genetic structure and variability of the working dog inferred from microsatellite marker analysis - Yun-Jeong Kwon; Bong-Hwan Choi; Jungwoo Eo; Choongrak Kim; Yi-Deun Jung; Ja-Rang Lee; Yuri Choi; Jeong-An Gim; Dong-Hoon Lee; Ji-Hong Ha; Dae-Soo Kim; Jae-Won Huh; et al. (Genes & Genomics, 2014)

Identification and characterization of transposable elements inserted into the coding sequences of horse genes - Kung Ahn; Jin-Han Bae; Jeong-An Gim; Ja-Rang Lee; Yi-Deun Jung; Kyung-Do Park; Kyudong Han; Byung-Wook Cho; Heui-Soo Kim (Genes & Genomics, 2013)

Association of Polymorphism in the Promoter of the Melatonin Receptor 1A Gene with Schizophrenia and with Insomnia Symptoms in Schizophrenia Patients - Hae Jeong Park; Jin Kyung Park; Su Kang Kim; Ah-Rang Cho; Jong Woo Kim; Sung-Vin Yim; Joo-Ho Chung (Journal of Molecular Neuroscience, 2011)

Regional distribution of perceived temperatures estimated by the human heat budget model (the Klima-Michel model) in South Korea - Jiyoung Kim; Kyu Rang Kim; Byoung-Cheol Choi; Dae-Geun Lee; Jeong-Sik Kim (Advances in Atmospheric Sciences, 2009)

Transcriptome analysis of human gastric cancer - Jung-Hwa Oh; Jin Ok Yang; Yoonsoo Hahn; Mi-Rang Kim; Sang-Soon Byun; Yeo-Jin Jeon; Jeong-Min Kim; Kyu-Sang Song; Seung-Moo Noh; Sangsoo Kim; Hyang-Sook Yoo; Yong Sung Kim; et al. (Mammalian Genome, 2005)